F(x) = 5x^2 + 9x – 4
g(x) = – 8x^2 – 3x – 4
Find (f + g)(x).
1 answer:
Answer:
(f + g)(x) = – 3x^2 + 5x - 8
Step-by-step explanation:
(f + g)(x) = f(x) + g(x)
= 5x^2 + 9x – 4 + (– 8x^2 – 3x – 4)
= 5x^2 + 9x – 4 – 8x^2 – 3x – 4
Combine
= – 3x^2 + 5x - 8
You might be interested in
Answer: 12
Step-by-step explanation:
I believe that you can make at most 16 bowls of chicken noodle soup. Of course that’s what I think you are asking.
Answer:
the answer is 22
Step-by-step explanation:
-|-7|+|-2+17
the 7 becomes positive
(7|+|-2)+17
5+17
=22
A = 2+3a +6
a-3a = 8
-2a = 8
a = -8/2 = -4
Answer:
11/8 OR 1 3/8
Step-by-step explanation: